Development of E-book Stories Based on Local Wisdom Menyama Braya to Improve Global Diversity Character in the Dimension of Pancasila Student Profile - Ni Kadek Ena Juliatni; I Wayan Lasmawan; Desak Putu Parmiti (STKIP Taman Siswa Bima, 2025)
This study developed a Menyama Braya-based e-book to enhance the global diversity character within the Pancasila Student Profile for fourth-grade students at SD Negeri 3 Ubung. The e-book was designed using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. It integrates values of tolerance, mutual cooperation, and respect, featuring engaging illustrations, child-friendly language, and reflective activities. The study involved lecturers, teachers, and fourth-grade students, with data collected through questionnaires assessing content validity, media, design, language, acceptability, and effectiveness. The results indicate that the e-book is highly effective and practical for learning, with an achievement rate of 93.74% from content experts, 92.70% from media experts, 94.1% from teachers, and 95.41% from students. Effectiveness tests using pretests and posttests showed a significant improvement in students' learning outcomes (p < 0.05). In conclusion, the Menyama Braya e-book is effective in fostering the global diversity character among fourth-grade elementary school students.